4x+9=5x-6

Simple and best practice solution for 4x+9=5x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9=5x-6 equation:


Simplifying
4x + 9 = 5x + -6

Reorder the terms:
9 + 4x = 5x + -6

Reorder the terms:
9 + 4x = -6 + 5x

Solving
9 + 4x = -6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
9 + 4x + -5x = -6 + 5x + -5x

Combine like terms: 4x + -5x = -1x
9 + -1x = -6 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + -1x = -6 + 0
9 + -1x = -6

Add '-9' to each side of the equation.
9 + -9 + -1x = -6 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = -6 + -9
-1x = -6 + -9

Combine like terms: -6 + -9 = -15
-1x = -15

Divide each side by '-1'.
x = 15

Simplifying
x = 15

See similar equations:

| 5r^2-35r+30=0 | | 80+0.3x=60+0.8x | | 11x-5=6c-20 | | 3x-13=4(x-3)+8 | | -10x-5y=50 | | 3(y-6)=2-27 | | g=4+2x^2 | | (5)+(7)= | | g=4-2x^2 | | 4y*(11y-14)=6-3y | | (2x-1)(x-13)= | | 4(y-2)=10-2y | | 0=6a+48 | | 11n^2-7n-2=-6+8n^2 | | 3(x+9)=2x-6 | | 9(-24)-5((-24)-8)= | | 7.5x+3.3-2x-6.7= | | Axb=A+13-b | | x+7.72=963 | | 4x+7=2x-15 | | -4-3z=23 | | (3i)-(6i)=0 | | 7=8y-17 | | 3(b+3)=42 | | (x^2)-x+400=0 | | 2(a-3)=40 | | 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 |

Equations solver categories